Konsepsi Quantum Learning; Suatu Analisis Learning Styles - Syibran Mulasi; Warul Walidin; Syabuddin Syabuddin; Salami Mahmud (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Improving the quality of learning is something that must be done well in school education, students who have diverse learning styles must be the main factor of teacher attention in order to be able to give meaning to learning well. To improve learning outcomes, one of them is through the application of the quantum learning model in the teaching and learning process. This research aims to find answers to the question of the effectiveness of using quantum learning in schools. Penalitian conducted by reviewing a variety of relevant literature both from journals and direct findings in the field. The results of the study found that the implementation of quantum learning can improve the quality of learning and maximum student understanding, given the different learning styles of students can be facilitated through the implementation of quantum learning models, so that learning styles are very supportive of quantum learning models and get perfect learning outcomes than conventional learning models.